Zeolitic Imidazolate Framework Derived Nanoparticles in Nitrogen-Doped Porous Carbon as a Highly Active and Durable Bifunctional Catalyst for Oxygen-Reduction and Evolution Reactions in Alkaline Media. (1st June 2022) - Parkash, Anand; Kapoor, Aneel; Solangi, Nizamuddin; Abbasi, Irfan Ahmed; Solangi, Sorath; Naveed, Kanwal
Abstract : In order to facilitate the large-scale applications of rechargeable Zn-air batteries, non-noble-metal-based materials with high activity for oxygen reduction (ORR) and evolution reactions (OER) are highly needed for replacing noble-metal-based materials. Here, a new method is used for developing Cu-doped ZIF-67 (Cu/ZIF-67) nanoparticles and carbonizing at various temperatures (500 °C–900 °C). Benefiting from the doping of Cu nanoparticles on the surface of the ZIF-67 and the synergistic interaction between Cu and the underlying Co atoms, the Cu/Co-NC-800 electrocatalyst exhibits superior electrocatalytic activity for both ORR (Eo 0.98, E1/2 0.84 V) and OER (overpotential 0.278 V) and superior alkaline media stability relative to both prepared and commercial Pt/C (Eo 0.96 V). These insightful findings inspire new perspectives for economical-practical bifunctional oxygen electrocatalysts to be designed and synthesized rationally.